The Effect of Age and Gender on Fetuin-A and Some Biochemical parameters in Blood Sera of Iraqi patients with T2DM: A comparative study - Baghdad Science Journal (مجلة بغداد للعلوم)
The serum protein test includes measurement of the level of total protein(albumin, globulin). Fetuin-A is a blood protein made in liver. It can inhibit insulin receptor, enhance insulin sensitivity and make the individuals more likely to develop type 2 diabetes, then disorder in lipid profile (Total cholesterol(TC), low density lipoprotein cholesterol (LDL-c), high density lipoprotein cholesterol (HDL-c), Triglyceride(TG) and very low density lipoprotein cholesterol (VLDL-c) . To evaluate Fetuin-A, total protein, albumin, globulin, HbAlc and lipid profile in 200 adult and elderly Iraqi patients with type 2 Diabetes Mellitus were taken and compare them with 200 subjects as a healthy control. The laboratory analysis(for patients and control ) were performed to determine these parameters .The results show that FBG. HbA1c, Lipid profile for (patients and control) (except HDL-c) were increase with age with a significant difference (p0.05) between male and female. Serum total protein, globulin, Fetuin-A, increase with age while albumin decrease with age(in patients and control).